Binder-free Li-O2 battery cathodes using Ni- and PtRu-coated vertically aligned carbon nanofibers as electrocatalysts for enhanced stability - Syed Shoaib Hassan Zaidi; Sabari Rajendran; Archana Sekar; Ayyappan Elangovan; Jun Li; Xianglin Li (Nano Research Energy, 2023)
The development of an ideal cathode for Li-O2 battery (LOB) has been a great challenge in achieving high discharge capacity, enhanced stability, and longevity. The formation of undesired and irreversible discharge products on the surface of current cathode materials limit the life span of the LOB. In this study, we report the systematic electrochemical study to compare the performance of LOB employing a unique graphitic nanostructured carbon architecture, i.e., vertically aligned carbon nanofiber (VACNF) arrays, as the cathode materials. Transition metal (Ni) and noble metal alloy (PtRu) are further deposited on the VACNF array as electrocatalysts to improve the discharge/charge processes at the cathode. The structure of as-prepared electrodes was examined with the field emission scanning electron microscopy, high-resolution transmission electron microscopy, and X-ray photoelectron spectroscopy (XPS). The LOB with VACNF-Ni electrode delivered the highest specific and areal discharge capacities (14.92 Ah·g−1, 4.32 mAh·cm−2) at 0.1 mA·cm−2 current density as compared with VACNF-PtRu (9.07 Ah·g−1, 2.62 mAh·cm−2), bare VACNF (5.55 Ah·g−1, 1.60 mAh·cm−2) and commercial Vulcan XC (3.83 Ah·g−1, 1.91 mAh·cm−2). Cycling stability tests revealed the superior performance of VACNF-PtRu with 27 cycles as compared with VACNF-Ni (13 cycles), VACNF (8 cycles), and Vulcan XC (3 cycles). The superior cycling stability of VACNF-PtRu can be attributed to its ability to suppress the formation of Li2CO3 during the discharge cycle, as elucidated by XPS analysis of discharged samples. We also investigated the impact of carbon cloth and carbon fiber as cathode electrode substrate on the performance of LOB.